Recovery-oriented nursing service for people with schizophrenia in the community: An integrative review - Jutharat Thongsalab; Jintana Yunibhand; Penpaktr Uthis (Belitung Nursing Journal, 2023)
Background: The recovery-oriented service concept has been recognized for its impact on mental health practices and services. As the largest group of mental healthcare providers, mental health nurses are well-positioned to deliver recovery-oriented services but face challenges due to role ambiguity and identity issues. Therefore, clarifying the role and principles of mental health nursing is essential. Objective: This study aimed to identify essential nursing practices for individuals with schizophrenia in recovery-oriented mental health services. Design: The study utilized a five-step integrative review approach, including problem identification, literature search definition, critical analysis of methodological quality, data analysis, and data presentation. Data Sources: Multiple databases, such as ScienceDirect and Scopus, as well as online libraries and journals/publishers, including Sage journals, APA PsyNet, SpringerLink, PsychiatryOnline, Taylor & Francis Online, and Wiley Online Library, were searched. The search spanned from the inception of the recovery-oriented services concept in 1993 to 2022. Review Methods: Content and thematic analysis were employed to analyze and synthesize the findings from the included studies. Results: Twenty-four articles met the inclusion criteria. Two themes were identified: 1) Direct nursing care, consisting of six sub-themes: therapeutic nurse-patient relationship (TNPR), psychoeducation (PE), coping skill training (CST), cognitive behavioral techniques (CBT), interventions to improve medication adherence (IMA), and social functioning (SF); and 2) Indirect nursing care. Conclusion: This study highlights the crucial role of nursing and nursing practices in recovery-oriented services. Mental health nurses prioritize person-centered care, therapeutic relationships, and collaboration with peer support workers to enhance treatment effectiveness. In addition, they focus on improving medication adherence, providing coping support, and promoting social capabilities, ultimately improving individuals’ quality of life. Aligning actions with recovery-oriented principles, mental health nurses emphasize empowerment and holistic care. Further research in this area will enhance the healthcare system and better support individuals on their recovery journey.